Sentencing for Youthful Offenders: The Impact of Youthfulness on the Sentencing Decisions - Du, Yu (Crime & delinquency, 2025)
Long held legal distinctions treat individuals under the age of 18 years differently than those over 18. However, neuroscience indicates that an individual’s brain may not be fully mature until 25 years. This brain immaturity suggests emerging adults may be more risk-seeking, impulsive, and less likely to appreciate the consequences of their acts. Because culpability for one’s actions is a key component of sentencing decisions, we hypothesize youthfulness (e.g. ages between 18 and 25 years) may mitigate judicial sentencing of this group. We analyze 5-year data from the Pennsylvania Commission on Sentencing. Our results indicate youthful offenders are more likely to get harsher punishment. The potential impacts of these results on other aspects of judicial sentencing and the youthful offenders sentenced were discussed.